China’s Opportunity: Recommendations for Liberal Arts Innovation - Godwin, Kara A.; Pickus, Noah (International Higher Education, 2018)
This article is based on CIHE Perspectives No. 8: “Liberal Arts & Sciences Innovation in China: Six Recommendations to Shape the Future,” available in English and Chinese.